Socio Economic Development Inequality and Its Impact on Poverty Levels in North Sumatra, 2019–2023: An Inter-District/City Study - Mutiara Fahmi; Hardiansyah Tambunan (JURNAL EQUILIBRIUM, 2026)
This research analyses the effects of disparities in the socio-economic development of 33 districts and cities in the province of North Sumatra on the poverty rate from 2019 to 2023. Employing panel data analysis, the study combines important variables for the development of the province, including education infrastructure, life expectancy, access to electricity, GRDP per capita, and the Human Development Index (HDI). The disparity in inter-district differences in economic capacity is measured through the Coefficient of Variation (CV) and the Williamson Index (WI). The findings indicate the high inequality in economic capacity in the districts, as measured through the high CV and WI values. On the other hand, the panel regression results show that the poverty rate in North Sumatra is mainly influenced by the structural and long-run differences between the districts, measured by the incredibly high intraclass correlation (rho 0.99). The negative effects of life expectancy, access to electricity, and the Human Development Index on the poverty rate suggest that improvements in human development achievements and infrastructure are very important factors in overcoming poverty. Conversely, GRDP and the number of schools had only minor impacts, suggesting that economic growth and the development of educational infrastructure are not directly associated with poverty reduction unless they are accompanied by improvements in quality and inclusivity.